Asas Pemungutan Pajak Dalam Pajak Penghasilan Transaksi Saham di Bursa - Bangkit Cahyono (LPPM-STPI, 2021)
Tax collection ideally can meet the principle of tax collection as submitted by Adam Smith is the principle of equality, certainty principle, the principle of convinience of payment, and the principle of effeciency. Income tax imposed on income is additional economic capability received or obtained Taxpayer. While the provisions on the collection of Income Tax on the Sale of Stock Transactions in the Stock Exchange shall be final and calculated with a certain percentage multiplied by the amount of transactions. It is interesting to be analyzed on the application of the four tax collection principles according to Adam Smith against the provision of Income Tax on the sale of shares transaction in Indonesia Stock Exchange (IDX). The results of the analysis show that the four principles of equality tax collection are not met while the other three principles are met. Given the tax function (budgetair) provisions on the collection of Income Tax on transactions on stock sales in the Stock Exchange still needs to be maintained.